Financial performance and reporting quality of government-linked companies (GLCs) in Bursa Malaysia following the establishment of the Putrajaya Committee on GLC High Performance / Siti Munirah Rahmat - Rahmat, Siti Munirah (2013)
The objective of this study is to examine the impact towards government-linked companies (GLCs) upon establishment of the Putrajaya Committee on GLC High Performance in term of their financial performance and financial reporting quality. This study used matched-sample logistic regression of 41 GLCs over a 13-years period from 1999 to 2012 and empirically examines whether there is any improvement in the GLCs financial performance and financial reporting quality. The results support prior findings by indicating a positive relation between the audit financial reporting qualities with the post period of the transformation programme. In addition to that, the findings also show that firm size is significantly related with the earning quality. On the other hand, no significant evidence was found for the financial performance of the GLCs for the pre period of the transformation programme. This study concludes that the Putrajaya Committee on GLC High Performance had contribute to the increase in financial reporting quality of the GLCs financial report thus it provide more useful information to the users of the financial statement itself.